Intestinal parasites from fingernails of sidewalk food vendors - Suriptiastuti, Suriptiastuti; Manan, Widiastuti S. (Universa Medicina, 2011)
Intestinal infections with soil-transmitted helminths and protozoa are still prevalent in Indonesia, particularly in urban communities. Transmission of parasitic infections is effected directly or indirectly through objects contaminated with feces, including food, water, fingers and fingernails, indicating the importance of fecal-oral human-to-human transmission. Sidewalk food vendors (SFVs) preparing food for their customers are a potential source of infections with many intestinal helminths and protozoa. Compared to other parts of the hand, the area beneath fingernails harbors the most microorganisms and is most difficult to clean. The objective of this cross-sectional study was to determine the prevalence of intestinal parasites in fingernail dirt of SFVs and to identify the associated factors. This study involved 112 SFVs in the vicinity of Hospital X in Central Jakarta, and used microscopic examination of SFV fingernail dirt for determining species prevalence of intestinal parasites. This study showed that 94 samples out of 112 (83.9%) were positive for intestinal parasites; 60 samples (63.8%) represented single infections and 34 (36.2%) mixed infections. Ascaris lumbricoides eggs were found in 30 (26.8%) samples and Giardia lamblia cysts in 12 (17.89%). The highest prevalence was found in subjects with primary school education, among whom 20 (30.8%) had single infections of A. lumbricoides and 16 (24.6%) mixed infections with A. lumbricoides and Trichuris trichiura. In conclusion, prevalence of intestinal parasites in SFV fingernail dirt is extremely high, with the highest prevalence among less educated SFVs. It is recommended to provide health education and training to all SFVs.